Rethinking western India : the changing contexts of culture, society and religion - Deak, Dusan, Ed (New perspectives in South Asian history, 2014)
Contributed articles presented at the 13th International Conference on Maharashtra: Culture and Society, held in Bratislava, Slovakia in June 2010.